DNA Barcoding Jasminum Sambac, Jasminum Nitidum, and Nyctanthes Arbor-Tristis by Using ITS2 and trnH-psbA Genes - Chang, Kek Ning (2015)
Jasminum and Nycianihes are from Oleaceae family which are widely cultivated and distributed all around the world especially Asian countries. The chemical constituents from the plants of Oleaceae family Jasminuin and Nyctanthes have high commercial value because it can be used in the pharmaceutical industry. Jasminum and Nyctanthes arc a source of essential oil and perfume due lo its fragrant smell. They can also be processed to make tea and food flavorings. Jasminum and Nycranthes though from the same family are in different genus though the phylogenetic position of Nyctanthes has been debated. By using DNA barcoding, we can determine the differences within and between species. Three different species of plants which are Jasminum sambac, Jasminum nitidum and Nyctanthes arbor-tristis were analysed using the Internal Transcribed Spacer 2 (ITS2) and trnH-psbA. The DNA samples were amplified using Polymerase Chain Reaction (PCR) for ITS2 and trnH-psbA gene sequences. The PCR products were sequenced, and then the results were analysed using T-Coffee, MEGA 6 and BLAST. Based on the results, J.sambac and J.nitidum shows higher similarity (0.128 for ITS2; 0.032 for rrnH-psbA) compared to N.arbor-tristis and Jasminum (Average=0.301 for ITS2; Average=0.237 for trnH-psbA) because J.sambac and J.nitidum come from the same genus, and this is one of the criteria for a good barcode.